(untitled) - Tolkien, J.R.R (New York, 1987)
To protect a magic ring, Frodo, the hobbit, must undertake a long and danerous journey
Keywords: Wizards,Magicians,Fantasy fiction, English,Phù Thủy,Pháp sư,Tiểu thuyết viễn tưởng Anh; Drama,Drama,Phim,Phim